Detection, Isolation and Antimicrobial Testing of Listeria monocytogenes in Chicken from Supermarket - Yew Huat Tang, John; Amirah Ismail, Aisyah; Afiza Badaluddin, Noor (International Journal of Engineering and Technology, 2018)
Listeria monocytogenes play a vital role in causing an infrequent and sometimes deadly foodborne disease known as Listeriosis. In this study, the presence of L. monocytogenes in chicken at supermarket and the antimicrobial susceptibility of the pathogen were determined. Detection of L. monocytogenes in chickens from supermarket was carried out using real time PCR and isolation of L. monocytogenes by plating onto PALCAM agar. The L. monocytogenes isolates were tested against 14 antibiotics for resistance determination using disc diffusion method. From 56 chicken samples tested, 35.7 % of the samples were detected contained the pathogen using real time PCR. Only 15 samples Â (26.8%) were positive for L. monocytogenes isolates. The isolates showed high resistance towards Penicillin G (100%), Ampicillin (93%), Rifampicin (93%), Ceftazidime (87%), Erythromycin (87%), and Tetracycline (80%). All the isolates were found to have the Multiple Antibiotic Resistance (MAR) index more than 0.2 which indicates multiple resistance towards antibiotics. In conclusion, L. monocytogenes was found in the chicken at supermarket and the isolates were found to be highly resistance towards multiple antibiotics. Thus, chicken meat must be properly cooked before consumption to prevent foodborne infection.Â